POTENTIAL USES OF BLOCKCHAINS IN HUMAN RESOURCES - Nagy, Peter (Applied Studies in Agribusiness and Commerce, 2023)
Blockchain technology offers businesses many opportunities for more efficient operation and safer data management. It also becomes easy tostore and share employee data, while the blockchain guarantees that it does not fall into unauthorized hands. The management of financial transactions and the automation of the payment process are also a great advantage for businesses, which can manage the payment of wages andbenefits more efficiently. Another area of application of blockchain technology is the creation of more efficient workflows that can improve productivity and reduce costs. The management of work schedules and optimized work processes will also be easier with the help of the blockchain, so businesses can become more efficient and effective. In this article, the relationship between HR and blockchains was explored through a meta-analysis based on available related publications.